Odpowiedź:
1]
a=(y2-y1)/(x2-x1)= ( -4-3)/(-2+1)= 7
y=ax+b
3=-1*7+b b= 10
y=7x +10
2a)
gdy a>0 funkcja rosnaca, gdy a=0 stała, gdy a<0 malejąca
a) a= 7 rosnaca
b) a= 3-√11 <0 malejaca
3]
y= 2(x+3)-5= 2x+6-5
y= 2x+1
4]
-2x-6=0 2x=-6 x=-3= m-ce zerowe
5]
a1=-2 a1*a2=-1= warunek prostopadłosci prostych
a2= 1/2
y=ax+b
-2=1/2*3+b
b= -2-3/2=- 7/2
y= 1/2 x -7/2
6]
y=3x-4 3x-y-4=0 A= 3 B=-1 C=-4
d=?
d=I A x+By + C I /√(A²+B²)= I 3*2-4*(-1) -4 I /√(3²+(-1)²)= 6/√10=6√10/10=
3√10/5
Szczegółowe wyjaśnienie: